O.I. Moskalskaya’s Legacy in Complex Sentence Theory: Development and Impact in Russian German Studies - O. A. Kostrova (Дискурс профессиональной коммуникации, 2025)
The theoretical contributions of Olga I. Moskalskaya to the study of German complex sentences (CS) represent a foundational yet often overlooked area in Russian Germanistics. Understanding the structure and function of CS is paramount for achieving clarity and precision in professional discourse, yet a comprehensive historical account of Moskalskaya’s pioneering work and its subsequent influence has been lacking. This article provides the first systematic analysis of Moskalskaya’s theory of CS, particularly her novel perception of CS as holistic linguistic units and their textual arrangement. It further aims to trace the development of her ideas in contemporary Russian German studies, filling a gap in the discipline’s history. The research draws upon Moskalskaya’s theoretical publications, seminal works by preceding and subsequent Germanists, and illustrative empirical data. Corpus data from the Digital Dictionary of the German Language (DWDS) were used to validate Moskalskaya’s CS-models and assess their frequency in modern German. Targeted samples from contemporary German novels (Walser, Schlink) illustrate CS functioning in text. Methodologically, the study combines an analysis of Moskalskaya’s CS-modeling with comparative, statistical, and transformational analyses of the illustrative material. The study first systematizes Moskalskaya’s theoretical positions on CS structure and textual function. It then demonstrates that the development of her ideas proceeded along two main trajectories: 1) enhanced understanding of CS wholeness, incorporating syntactic-pragmatic, metacognitive, and illocutionary perspectives; and 2) continued investigation into CS functions in numerous textual and discursive contexts, including their role in information structuring and conveying speaker stance. This research also underscores the lasting impact of Moskalskaya’s works. By demonstrating the theoretical grounding and developmental pathways of CS analysis, the findings offer perspectives for contemporary linguistic research. Understanding CS is crucial for enhancing the efficacy and precision of German-language professional communication, particularly in academic, technical, and diplomatic discourse.